Construction of conductive multilayer films of biogenic triangular gold nanoparticles and their application in chemical vapour sensing - Singh, Amit; Chaudhary, Minakshi V.; Sastry, Murali (Nanotechnology, 2006)
Metal nanoparticles are interesting building blocks for realizing films for a number of applications that include bio- and chemical sensing. To date, spherical metal nanoparticles have been used to generate functional electrical coatings. In this paper we demonstrate the synthesis of electrically conductive coatings using biologically prepared gold nanotriangles as the building blocks. The gold nanotriangles are prepared by the reduction of aqueous chloroaurate ions using an extract of the lemongrass plant (Cymbopogon flexuosus) which are thereafter assembled onto a variety of substrates by simple solution casting. The conductivity of the film shows a drastic fall upon mild heat treatment, leading to the formation of electrically conductive thin films of nanoparticles. We have also investigated the possibility of using the gold nanotriangle films in vapour sensing. A large fall in film resistance is observed upon exposure to polar molecules such as methanol, while little change occurs upon exposure to weakly polar molecules such as chloroform.

Scanning tunneling microscopy/spectroscopy on Au nanoparticles assembled using lauryl amine (LAM) and octadecane thiol (ODT) - Datar, Suwarna; Chaudhary, Minakshi V.; Sastry, Murali; Dharmadhikari, C. V. (Applied Surface Science, 2007)
In this report, we demonstrate scanning tunneling microscopy and spectroscopy on thin filins of lauryl amine (LAM) and octadecane thiol (ODT) protected gold nanoparticles. We show that the zero current in the I-V curves (measure of Coulomb blockade (CB) of the nanoparticles) depends on the properties of the spacer molecule. In both the cases the gap voltage and the tunneling current at which the images are obtained are quite different which is further confirmed from the fitting performed based on the orthodox theory. The values for the capacitance and charging energy obtained from the fitting for ODT capped particles are comparable to the values obtained using spherical capacitor model. In contrast, values of these parameters were found to differ for LAM capped nanoparticles. While imaging, ODT capped nanoparticles were observed to drag along the scan direction leading to ordering of particles. Images of LAM capped gold nanoparticles show local ordering in self-assembly of particles although no evidence of large scale ordering in spatial Fourier transform was seen. These observations suggest that nanoparticles with larger CB would be intaged nonevasively in contrast to small CB systems for which tip induced effects will be dominant. In both the systems the current was found to rise faster than theoretical curves based on the orthodox theory suggesting that mechanism of charge transfer in this case may involve field emission rather than tunneling through a rectangular barrier. An attempt has been made to explain charge transfer based on Fowler-Nordheim (F-N) plots of the I-V curves. (c) 2006 Elsevier B.V All rights reserved.
Keywords: Nanostructures; scanning tunneling microscopy (STM)

Chemically stable multilayered covalent organic nanosheets from covalent organic frameworks via mechanical delamination - Chandra, Suman; Kandambeth, Sharath; Biswal, Bishnu P.; Lukose, Binit; Kunjir, Shrikant M.; Chaudhary, Minakshi V.; BabaRao, Ravichandar; Heine, Thomas; Banerjee, Rahul (Journal of the American Chemical Society, 2013)
A series of five thermally and chemically stable functionalized covalent organic frameworks (COFs), namely, TpPa-NO2, TpPa-F-4, TpBD-(NO2)(2), TpBD-Me-2, and TpBD-(OMe)(2) were synthesized by employing the solvothermal aldehyde-amine Schiff base condensation reaction. In order to complete the series, previously reported TpPa-1, TpPa-2, and TpBD have also been synthesized, and altogether, eight COFs were fully characterized through powder X-ray diffraction (PXRD), Fourier transform IR (FT-IR) spectroscopy, C-13 solid-state NMR spectroscopy, and thermogravimetric analysis. These COFs are crystalline, permanently porous, and stable in boiling water, acid (9 N HCl), and base (3 N NaOH). The. synthesized COFs (all eight) were successfully delaminated using a simple, safe, and environmentally friendly mechanical grinding route to transform into covalent organic nanosheets (CONs) and were well characterized via transmission electron microscopy and atomic force microscopy. Further PXRD and FT-IR analyses confirm that these CONs retain their structural integrity throughout the delamination process and also remain stable in aqueous, acidic, and basic media like the parent COFs. These exfoliated CONs have graphene-like layered morphology (delaminated layers), unlike the COFs from which they were synthesized.

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film

Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets